Meramec velocity systematics - Fu, Jing (My University, 2020)
Elastic wave velocities are often used to interpret formation properties, such as porosity, mineralogy, and lithology. Shear wave velocity systematics are valuable in creating elastic models when only P-wave sonics exists in legacy wells. Although considerable research has been carried out on conventional reservoir velocity systematics, the systematics for unconventional formations remain ill-defined. In this study, a Vs-Vp systematic is developed for the Meramec formation, using laboratory pulse transmission ultrasonic measurements. The influences of porosity and mineralogy on velocities are discussed and a comparison between Meramec velocity systematic and existing literature systematics is provided. The Vp and Vs measurements on 385 dodecane saturated core samples (106 vertical and 279 horizontal plugs), from seven Meramec wells were acquired. Porosity and mineralogy were also measured on each core plug. We propose two approaches to estimate Vs from Vp: 1) ignoring anisotropy, we combine both Vp and Vs measurements from all vertical plugs and low anisotropy horizontal plugs to create a single systematic, and 2) considering anisotropy, Vp measurements from horizontal plugs were corrected based on the Thomsen’s compressional wave anisotropy parameter and the systematics were generated. The Meramec formation has weak shear wave anisotropy, typically < 10%. The analysis shows that velocities are more sensitive to porosity than mineralogy by a factor of approximately 10. The Vp and Vs dependencies are shown below, for dodecane saturated samples (∅ is the volume fraction pores, C is the weight fraction clay, using vertical and horizontal samples with low anisotropy): Vp=6.4-1.5C-15.5porosity Vs=3.6-0.9C-5.1porosity The shear wave systematics for dodecane saturated measurements are (All velocities are km/s.): Method 1: Vs= 0.90 + 0.42Vp Method 2: Vs= 0.20 + 0.56Vp The first equation has a smaller residual and estimated error than the second equation. Using the first equation, the Meramec velocity systematic shows good agreement with dipole wireline measurements even though there is a substantial difference in measurement frequencies. The Meramec velocity systematics are considerably different from published systematics. Seven Meramec layers can also be grouped into three groups based on the Vp-Vs equations and lithology. The Meramec shear-wave systematics can be applied in wireline and seismic analyses. The result shows that the method of ignoring anisotropy provides a better Vs estimation than the method considering anisotropy. However, the second method can be potentially applied to a formation that has high anisotropy. Applying Castagna's mudrock equation, using compressional wave velocity to predict shear wave velocities yield an estimation error 6% to 16% in Vs. It is critical to generate specific velocity systematics which are calibrated to the formation of interest.
Keywords: Meramec; Petrophysics; Ultrasonic